The extended impact of the COVID-19 pandemic on medical imaging case volumes: a retrospective study - Alhazmi, Fahad H.; Alrehily, Faisal A.; Alsharif, Walaa; Gameraddin, Moawia; Alsultan, Kamal D.; Alsaedi, Hassan Ibrahim; Aloufi, Khalid M.; Alshoabi, Sultan Abdulwadoud; Abdulaal, Osamah M.; Qurashi, Abdulaziz A. (PeerJ, 2025)
Objective This study aims to investigate the long-term effects of the COVID-19 pandemic on medical imaging case volumes. Methods This retrospective study analyzed data from the Integrated Radiology Information System-Picture Archive and Communication System (RIS-PACS), including monthly medical imaging case volumes at a public hospital, spanning from January 2019 to December 2022. The study collected data on medical imaging examinations, comparing the pre COVID-19 period, which acted as a control group, with the periods following COVID-19, which were designated as cohort groups. Results The total number of medical imaging procedures performed (n = 597,645) was found significantly different (F = 6.69, P < 0.001) between 2019 and 2022. Specifically, the bone mineral density/computed radiography (BMD/CR) modality experienced a significant decrease (P = 0.01) of the procedures performed in 2020 and 2021 compared to 2019. Conversely, the nuclear medicine/computed tomography (NM/CT) and computed tomography (CT) modalities demonstrated a significant increase of the procedures performed in 2021 (P = 0.04) and (P < 0.0001), respectively, and in 2022 (P = 0.0095) and (P < 0.0001), respectively, compared to the pre-pandemic year. The digital X-ray modality (DX) showed the highest volume (67.63%) of the performed procedures overall between 2019 and 2022. Meanwhile, magnetic resonance imaging (MR) and ultrasound (US) modalities experienced a slight drop in the number of procedures in 2020—4.47% for MR and 1.00% for US, which subsequently recovered by 22.15% and 19.74% in 2021, and 24.36% and 17.40% in 2022, respectively, compared to 2019. Conclusion The COVID-19 pandemic initially led to a drop in the number of medical imaging procedures performed in 2020, with the most noticeable drop occurring during the early waves of the pandemic. However, this trend revealed a gradual recovery in the subsequent years, 2021 and 2022, as healthcare systems adapted, and pandemic-related restrictions were modified.
Keywords: Radiology; Medical imaging; COVID-19; Pandemic